Measuring BUMDes Performance to Optimize Village Economic Growth - Wahyu Maulana; Moh. Amir Furqon; Purwanto Purwanto (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2023)
A village with evenly distributed economic growth is an achievement in itself, as seen by the presence of BUMDes. This does not work easily, there are deficiencies and limitations so that the existence of BUMDes can make a positive contribution to a more independent village and grow its economy. The research objective is to measure the performance of BUMDes. The object of research is BUMDes Delta Mulia in the village of Panempan Pamekasan. The research method is in the form of quantitative descriptive using a combination of analysis Malcolm Baldrige and Du Pont System in producing BUMDes performance analysis. The results of the research show that the financial aspect resulted in a decrease in performance from 2018 to 2021. The average calculation shows a result of 28.38% where this figure is below the 30% standard, which means that the performance is not optimal. From the non-financial aspect, it generates 844 points out of a maximum total of 1000 points which means that BUMDes performance is in the Benchmark Leader criteria. From the results of this study, BUMDes can carry out performance evaluations, especially on financial aspects so that their performance is better and as good as performance on non-financial aspects